Enhancement of the Supplementary Method for Solving Problems in Partial Linear Programming - Dina Saad Faraj (Bilangan : Jurnal Ilmiah Matematika, Kebumian dan Angkasa, 2024)
The presented paper introduces an enhanced approach to find the available solution(s) for fractional linear programming problems (FLPP). While the common approach relies on considering the elements at the numerator and denominator to construct tables D1 and D2, followed by finding theirs and the Ze values, the new approach could be used to minimize the tables and decrease the calculation times and complicity.